The timing of financing decisions: An examination of the correlation in financing waves☆ - DITTMAR, A; DITTMAR, R (Journal of Financial Economics, 2008)
Why do corporate financing events occur in waves? We challenge recent evidence of the importance of valuation cycles in driving financing waves by documenting that the aggregate pattern of stock repurchases mirrors that of equity issuance and mergers, despite repurchases involving an opposite transaction. We then show that trends in financing decisions result from differing responses to the same economic stimulus: growth in GDP. Specifically, economic expansion reduces the cost of equity relative to the cost of debt, inducing firms to issue equity, and increases cash flow and also causes varying degrees of uncertainty, increasing stock repurchases. We document similar trends and provide similar motivation for merger waves.